Multi-source solid waste composite filling cementing material, preparation method thereof and filling material containing multi-source solid waste composite filling cementing material

By combining sodium sulfate modified gypsum with a variety of solid waste, a sulfate and alkaline reaction system is constructed, which solves the filling difficulties and high cost problems caused by fine tailings, and improves the water retention performance and later strength of the gelling material , achieving cost reduction and performance improvement.

CN119241191AActive Publication Date: 2025-01-03CHANGCHUN GOLD RES INST

Patent Information

Application Number
CN202411378494.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-03
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

The tailings produced by the mine plant are fine in size and poor permeability, which leads to difficulty in sedimentation and concentration of slurry during mine filling, low dehydration efficiency in mining sites, slow development of filling strength, and high cost of filling gelling materials.

Method used

Sodium sulfate is used to modify the gypsum separated and extracted from the biological oxidation liquid, combine with various solid wastes such as water slag and fly ash, design reasonable raw material components and ratios, and prepare multi-source solid waste composite fill gelling materials, through sulfuric acid Salt and alkaline reaction systems improve the water retention and late strength of gelled materials.

Benefits of technology

It effectively improves the water retention performance of the gelling material and the later strength of the filler, reduces costs, solves the problems of slow settling time and low early strength of the tailings filling, and can replace traditional cement products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005069286540000101
    Figure BDA0005069286540000101
  • Figure BDA0005069286540000111
    Figure BDA0005069286540000111
  • Figure BDA0005069286540000131
    Figure BDA0005069286540000131
Patent Text Reader

Abstract

The invention provides a multi-source solid waste composite filling cementing material, a preparation method thereof and a filling material containing the multi-source solid waste composite filling cementing material, and belongs to the field of building materials. According to the invention, sodium sulfate is utilized to modify gypsum separated and extracted from biological oxidation liquid, raw material components and proportion are reasonably designed, gypsum, water granulated slag, fly ash and other solid wastes are mixed, and the use cost of the cementing material is effectively reduced. The multi-source solid waste composite filling cementing material comprises the following raw materials in parts by weight: 15.5-20.5 parts of gypsum powder, 10-15 parts of sodium sulfate, 22.5-27.5 parts of water granulated slag micro powder, 22.5-27.5 parts of fly ash, 2.5-7.5 parts of cement clinker, 7.5-12.5 parts of quick lime and 0.5-2 parts of an active excitant, the cementing material contains more active components, the hydration speed is high, multiple hydration products are generated, the setting time is short, and the cementing material is suitable for large-scale production. And the filling material prepared from the material has high strength index.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of building materials, and in particular to a multi-source solid waste composite filling cementitious material, a preparation method thereof, and a filling material containing the material. Background Art

[0002] Tailings are solid waste discharged by the mine dressing plant after grinding the ore to extract valuable elements. Using tailings as aggregate and mixing with cementitious materials to backfill the goaf is an important way for mines to dispose of large amounts of solid waste. However, with the continuous improvement of mineral processing recovery rate, the particle size of tailings produced by the dressing plant is getting finer and finer. The fine particle size and poor permeability of tailings themselves have led to long-term problems in the sedimentation and concentration of slurry, low dehydration efficiency in the mine field, and slow development of filling strength in mine filling.

[0003] On the other hand, as cement prices rise, the cost of filling gelling materials also remains high. Using solid waste instead of industrial raw materials to prepare filling gelling materials is one of the current areas of focus for technical personnel. This solution can not only realize the resource utilization of waste, but also reduce the preparation and use costs of filling gelling materials, which is of great significance to promoting green mine construction. However, how to adjust the raw material ratio and preparation method of filling gelling materials to improve the filling performance of this filling gelling material still needs further research and solution.

[0004] In view of this, it is necessary to design a multi-source solid waste composite filling cementitious material and a preparation method thereof and a filling material containing the material to solve the above problems. Summary of the invention

[0005] In view of the technical problems existing in the background technology, the present application uses sodium sulfate to modify the gypsum separated and extracted from the biological oxidation liquid, rationally designs the raw material composition and ratio, mixes various solid wastes such as gypsum, slag, fly ash, etc., and provides a multi-source solid waste composite filling cementitious material and its preparation method and filling material containing the material, aiming to solve the problems of difficulty in slurry sedimentation and concentration in mine filling, low dehydration efficiency in the mining area, slow development of filling body strength, and excessively high cost of filling cementitious materials.

[0006] In a first aspect, the present application provides a method for preparing a multi-source solid waste composite filling cementitious material, comprising the following steps:

[0007] S1, mixing the water slag and water in a mass ratio of (0.8-1.2):1 to form a slag slurry, pouring it into a ball mill for mechanical activation, putting it into an oven for drying, then grinding and sieving to obtain water slag micro powder;

[0008] S2, preparing a sodium sulfate solution with a concentration of 30%-80%, spraying the sodium sulfate solution uniformly on the gypsum surface without dead angles according to the expected weight portion through a spray device, drying in an oven and then grinding to obtain gypsum powder with a fineness greater than 200 mesh;

[0009] S3, uniformly mixing sodium hydroxide and water glass in a mass ratio of (0-3):4 to obtain an active activator;

[0010] S4, mixing and stirring the gypsum powder, the slag powder, the active activator, fly ash, cement clinker and quicklime according to the expected weight proportions to obtain the multi-source solid waste composite filling cementitious material.

[0011] In some embodiments, in step S1, the mechanical activation time is 30 min-50 min, the sieving is to sieve the water slag with 200 mesh by vibration sieving method, and the oven is set to 100-105° C. for 24-28 hours; the activity coefficient of the water slag powder is ≥0.25, and the specific surface area is ≥600m 2 / kg.

[0012] In some embodiments, in step S3, the water glass is industrial powdered sodium silicate with an effective content greater than 95% and a modulus of 1.5; the sodium hydroxide is industrial powdered sodium hydroxide with an effective content greater than 90%.

[0013] In some embodiments, in step S2, the oven is set to 100-105° C. for 12-16 hours, and the sodium sulfate solution is prepared using industrial powdered sodium sulfate with an effective content greater than 90%.

[0014] In some embodiments, in step S4, the cement clinker is silicate cement clinker, and the CaO, SiO 2 、Al 2 O 3 and Fe 2 O 3 The total mass proportion of is greater than 95%; the quicklime is calcareous quicklime in which the mass proportion of CaO exceeds 60%.

[0015] In the second aspect, the embodiment of the present application provides a multi-source solid waste composite filling cementitious material, which is prepared according to any one of the aforementioned schemes, and the multi-source solid waste composite filling cementitious material includes the following raw materials in parts by weight: 15.5-20.5 parts of gypsum powder, 10-15 parts of sodium sulfate, 22.5-27.5 parts of slag powder, 22.5-27.5 parts of fly ash, 2.5-7.5 parts of cement clinker, 7.5-12.5 parts of quicklime, and 0.5-2 parts of active stimulant. The gypsum powder is prepared by using gypsum separated and extracted from biological oxidation liquid.

[0016] In some embodiments, the initial setting time of the net slurry of the multi-source solid waste composite filling cementitious material is 40-50 minutes, and the final setting time is 380-400 minutes.

[0017] In a third aspect, an embodiment of the present application provides a filling material, including the multi-source solid waste composite filling cementitious material and tailings in the aforementioned scheme.

[0018] In some embodiments, the tailings include ultra-fine gold tailings or tailings with a fineness of 100-400 mesh.

[0019] In some embodiments, the expansion of the filling material is 20-50 cm and the later strength is 2.3-2.5 MPa.

[0020] The beneficial effects of this application are:

[0021] (1) This application uses gypsum separated and extracted from the biological oxidation liquid as the base material, and also utilizes other industrial solid wastes such as slag and fly ash, which not only reduces the consumption of non-renewable resources such as cement, but also improves the utilization rate of waste resources, solves the storage and treatment problems of gypsum byproducts generated during the treatment of biological oxidation liquid, and conforms to the concept of green and waste-free production. Since the cost of this gypsum is much lower than that of the same type of cement, the cost of filling gel materials is further reduced, creating new economic benefits for enterprises.

[0022] (2) The preparation method of the multi-source solid waste composite filling cementitious material provided in the present application utilizes sodium sulfate to modify the gypsum separated and extracted from the biological oxidation liquid, rationally designs the raw material composition and ratio, effectively improves the water retention performance of the cementitious material, and greatly improves the later strength of the cementitious material and the filling material. The preparation method provided in the present application is simple and efficient, and is convenient for industrial production.

[0023] (3) The multi-source solid waste composite filling cementitious material provided by this application can be used for ultra-fine tailings filling in gold mines, and can directly replace the mainstream cement products currently used for mine filling. It has finer particle size, more active ingredients, and faster hydration speed, and can effectively solve the problems of slow setting time and low early strength of ultra-fine tailings filling. When used for filling other tailings with coarser grading, the mechanical force activation time of water slag in the multi-source solid waste composite filling cementitious material can be appropriately reduced.

[0024] (4) The setting time of the multi-source solid waste composite filling cementitious material prepared in this application is shorter than that of P.O42.5 ordinary Portland cement paste, and the expansion of the filling material prepared using the cementitious material is 20-50cm, and the later strength is 2.3-2.5MPa, both of which are better than the filling material prepared by P.O42.5 ordinary Portland cement paste.

[0025] The reason why the multi-source solid waste composite filling cementitious material has a short coagulation time and high strength of the filling material prepared by it is that there are two reaction systems in the coagulation process of this cementitious material. First, the gypsum powder and the water slag powder activated by mechanical force constitute a sulfate reaction system. In this system, gypsum provides a part of SO for the generation of hydration products. 4 2- As well as a suitable alkaline environment, another part of the reaction requires SO 4 2- Provided by sodium sulfate, in the reaction, gypsum and sodium sulfate simultaneously stimulate the water slag to generate calcium sulfoaluminate and calcium sulfoaluminate crystals. This method effectively improves the water retention performance of the cementitious material, and promotes the early and mid-term strength improvement of the filling material and the generation of early and mid-term hydration products; secondly, the present application also introduces fly ash, quicklime, cement clinker and active stimulant to form an alkaline reaction system, which accelerates the hydration rate of the material while increasing the number of later hydration products to generate hydrated calcium silicate gel, hydrated calcium silicate and other hydration products. The calcium sulfoaluminate generated in the early coagulation process and the hydrated calcium silicate gel generated in the later stage are continuously crystallized, which promotes the continuous progress of the reaction. At the same time, through the close interweaving of the two in the material, the later coagulation strength of the material is greatly improved.

[0026] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. DETAILED DESCRIPTION

[0027] The following is a detailed description of the embodiments of the technical solution of the present application. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the description and claims of this application and any variations thereof are intended to cover non-exclusive inclusions.

[0029] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0030] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0031] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0032] In recent years, due to the rising cement prices and insufficient tailings pond capacity, the filling and cementing costs of mining companies remain high. At the same time, as the recovery rate of mineral processing continues to increase, the tailings particle size is getting finer and finer. The fine tailings particle size and poor permeability lead to the problems of slurry sedimentation and concentration difficulties, low dehydration efficiency in the mine, and slow growth of filling strength in the mine filling.

[0033] The present application utilizes sodium sulfate to modify the gypsum separated and extracted from the biological oxidation liquid, rationally designs the raw material composition and proportion, mixes various solid wastes such as gypsum, slag, fly ash, etc., and provides a multi-source solid waste composite filling cementitious material and a preparation method thereof and a filling material containing the material, which effectively improves the water retention performance of the cementitious material, greatly improves the later strength of the cementitious material and the filling material, and reduces the use cost of the cementitious material.

[0034] In a first aspect, the present application provides a method for preparing a multi-source solid waste composite filling gelling material, comprising the following steps:

[0035] S1, mixing the slag with water in a mass ratio of (0.8-1.2):1 to form a slag slurry, pouring it into a ball mill for mechanical activation, putting it into an oven for drying, and then grinding it with a ball mill, sieving it, and obtaining slag micro powder;

[0036] S2, preparing a sodium sulfate solution with a concentration of 30%-80%, spraying the sodium sulfate solution uniformly on the gypsum surface without dead angles according to the expected weight portion through a spray device, drying it in an oven, and finally grinding it to a fineness greater than 200 mesh to obtain gypsum powder;

[0037] S3, uniformly mixing sodium hydroxide and water glass in a mass ratio of (0-3):4 to obtain an active activator;

[0038] S4, mixing and stirring the gypsum powder, slag powder, active activator, fly ash, cement clinker and quicklime according to the expected weight proportions to obtain the multi-source solid waste composite filling cementitious material.

[0039] Furthermore, in step S1, the mechanical activation time is 30 min-50 min, the slag is screened with 200 mesh by vibration screening method, and the oven is set at 100-105° C. for 24-28 h; the activity coefficient of the slag powder is ≥0.25, and the specific surface area is ≥600 m 2 / kg, meeting the requirements of national standards for slag used in cement production.

[0040] Further, in step S2, the oven is set at 100-105°C for 12-16 hours, the sodium sulfate solution is prepared using industrial powdered sodium sulfate with an effective content greater than 90%, and the concentration of the sodium sulfate solution should not be lower than 30%, otherwise too much water will be sprayed onto the gypsum, which will cause the gypsum drying time to be prolonged.

[0041] Further, in step S3, the water glass is industrial powdered sodium silicate with an effective content greater than 95% and a modulus of 1.5; and the sodium hydroxide is industrial powdered sodium hydroxide with an effective content greater than 90%.

[0042] Further, in step S4, the cement clinker is silicate cement clinker, and the CaO, SiO 2 、Al 2 O 3 and Fe 2 O 3 The total mass proportion of is greater than 95%; the quicklime is calcium quicklime in which the mass proportion of CaO exceeds 60%; and the stirring time is 400-600s.

[0043] In the second aspect, the present application provides a multi-source solid waste composite filling cementitious material, which is prepared by the preparation method described in any of the aforementioned technical schemes, and includes the following raw materials in weight proportions: 15.5-20.5 parts of gypsum powder, 10-15 parts of sodium sulfate, 22.5-27.5 parts of slag powder, 22.5-27.5 parts of fly ash, 2.5-7.5 parts of cement clinker, 7.5-12.5 parts of quicklime, and 0.5-2 parts of active stimulant.

[0044] The gypsum powder is prepared by using gypsum separated and extracted from biological oxidation liquid.

[0045] The production area for separating and extracting gypsum from biological oxidation liquid is generally not far from the production areas of solid wastes such as slag powder and fly ash. The material transportation cost and procurement cost are relatively low, which is conducive to industrial production and large-scale application.

[0046] Furthermore, in some embodiments, the initial setting time of the net slurry of the multi-source solid waste composite filling cementitious material is 40-50 minutes, and the final setting time is 380-400 minutes.

[0047] The multi-source solid waste composite filling cementitious material provided in the present application has two reaction systems during the coagulation process, one is the sulfate reaction system, which mainly exists in the early and middle stages of the coagulation process; the other is the alkaline reaction system, which mainly exists in the late stage of the coagulation process.

[0048] (1) Sulfate reaction system: The main raw materials involved in the reaction in this system are gypsum powder, slag powder and sodium sulfate. Gypsum provides part of SO for the formation of hydration products. 4 2- As well as a suitable alkaline environment, another part of the reaction requires SO 4 2- Provided by sodium sulfate. In the reaction, gypsum and sodium sulfate simultaneously stimulate the water slag to generate calcium sulfoaluminate and ettringite crystals. These two products can enhance the strength of the material in the early and middle stages of coagulation. In addition, a large number of water molecules are combined in the ettringite crystals, which effectively improves the workability of the material.

[0049] Although the above reaction system can enhance the strength of the material in the early and middle stages of coagulation, there are still some problems. First, the structure of calcium sulfonite, the main product of the above reaction system, is not stable and cannot guarantee the later strength of the material; second, a certain amount of by-product calcium sulfite will be produced during the reaction, which easily makes the material difficult to solidify; third, the content of Al and Si in the slag powder is relatively low, which is not conducive to the formation of a large number of hydration products in the later stage. Therefore, a second reaction system is needed to assist in improving the final coagulation strength of the material.

[0050] (2) Alkaline reaction system: The main raw materials involved in the reaction in this system are fly ash, cement clinker, quicklime, water glass and sodium hydroxide. Among them, fly ash contains more SiO 2 and Al 2 O 3 , which can provide Al and Si for the formation of hydration products in the later stage. In the reaction, first, the strong alkali sodium hydroxide dissolves and destroys the glass of fly ash to stimulate the activity of fly ash, and quicklime provides the Ca required for the reaction. 2+ and OH -, and increase the water temperature to speed up the hydration reaction; then, the cement clinker induces the hydration reaction, and under the stimulation of water glass, hydrated calcium silicate gel, hydrated calcium silicate and other hydration products are generated, among which hydrated calcium silicate gel is the main product; finally, the calcium aluminosilicate generated in the early coagulation process and the hydrated calcium silicate gel generated in the later stage continuously crystallize, which promotes the continuous progress of the reaction. At the same time, through the close interweaving of the two in the material, the later coagulation strength of the material is improved.

[0051] In a third aspect, the present application provides a filling material, which includes the multi-source solid waste composite filling cementitious material and tailings in the aforementioned scheme, and the tailings include gold mine tailings or other tailings with a fineness of 100-400 mesh.

[0052] Furthermore, in some embodiments, the expansion of the filling material is 20-50 cm, and the later strength is 2.3-2.5 MPa. The filling material is used for filling mining. At the same age, the strength index of the filling material exceeds the strength of the filling material prepared with P.O42.5 ordinary Portland cement by more than 20%.

[0053] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.

[0054] The raw materials used in the examples provided in this application are described as follows:

[0055] (1) Gypsum: An industrial by-product separated and extracted from biological oxidation liquid. It has a moisture content of about 15%, a pH value of 11-12, and contains relatively few toxic and harmful components. Its main chemical components are shown in Table 1.

[0056] Table 1. Main components of gypsum isolated and extracted from biological oxidation liquid (wt%)

[0057] element <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> CaO MgO <![CDATA[Fe 2 THE 3 ]]> <![CDATA[CaSO 4 ]]> content(%) 3.39 10.34 34.44 8.4 0.16 31.9 white As Cr Pb Cd other - content(%) 0.0015 0.0013 0.0062 0.00074 11.36 -

[0058] (2) The activity coefficient of the slag is ≥ 0.25, which meets the requirements of the national standard for slag used in cement production. Its main chemical composition is shown in Table 2.

[0059] Table 2. Main components of slag (wt%)

[0060] chemical composition <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> CaO MgO <![CDATA[Fe 2 THE 3 ]]> S C content(%) 21.31 11.26 46.13 6.31 0.49 2.58 0.24

[0061] (3) Fly ash: Class I general solid waste, can be used for underground filling, the main chemical composition is shown in Table 3.

[0062] Table 3. Main components of fly ash (wt%)

[0063] Chemistry 2 points <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> CaO MgO <![CDATA[Fe 2 THE 3 ]]> <![CDATA[K 2 The]]> C S content(%) 53.29 17.00 4.38 1.10 2.88 1.45 5.20 0.62

[0064] (4) Sodium sulfate: industrial powdered sodium sulfate with an effective content greater than 90%.

[0065] (5) Quicklime: Calcium quicklime with CaO accounting for more than 60%.

[0066] (6) Cement clinker: CaO, SiO 2 、A1 2 O 3 , Fe 2 O 3 Total content of Portland cement clinker greater than 95%.

[0067] (7) Water glass: Industrial powdered sodium silicate with an effective content greater than 95% and a modulus of 1.5.

[0068] (8) Sodium hydroxide: industrial powdered sodium hydroxide with an effective content greater than 90%.

[0069] It should be noted that there may be differences in composition between gypsum products separated and extracted from different biological oxidation liquids, and between gypsum products separated and extracted from different biological oxidation liquids and commercially available gypsum products. Similarly, there are such differences between slag and fly ash, which are both solid wastes, and commercially available products. This situation is inevitable. Therefore, in the specific implementation, the formula composition of this application should be appropriately adjusted according to the composition of the solid waste. People in this field should understand that such adjustments are within a reasonable range and do not affect the practicality of this application.

[0070] 1. Preparation method

[0071] Example 1

[0072] The present embodiment provides a multi-source solid waste composite filling cementitious material, including the following raw materials in parts by weight: 18 kg of gypsum powder, 13 kg of sodium sulfate, 26 kg of slag powder, 26 kg of fly ash, 6 kg of cement clinker, 10 kg of quicklime, and 1 kg of active stimulant.

[0073] This embodiment also provides a method for preparing a multi-source solid waste composite filling gelling material, the specific steps of which are:

[0074] S1, mix the water slag and water in a mass ratio of 0.8:1 and pour into a ball mill for 40 minutes of mechanical activation, then put the activated slag slurry into a drying oven at 105℃ for 24 hours to dry the water slag to constant weight, and then grind to obtain water slag powder. During the grinding process, the water slag powder is sieved with 200 mesh by vibration screening method, and the particle size of the water slag powder sample is detected by laser particle size analyzer to check whether the surface area of ​​the water slag powder exceeds 600m 2 / kg to ensure sufficient grinding.

[0075] S2, prepare sodium sulfate into a 30% concentration liquid, spray it evenly on the gypsum extracted from the biological oxidation liquid, and then put the gypsum into an oven at 105°C for 12 hours to make the gypsum dry to constant weight, and then grind it to obtain gypsum powder with a fineness greater than 200 mesh.

[0076] S3, uniformly mixing sodium hydroxide and water glass in a mass ratio of 1:4 to obtain an active activator.

[0077] S4, pour the slag powder, gypsum powder, active activator, sodium sulfate, fly ash, cement clinker and quicklime prepared in steps S1-S3 into a high-speed mixer in a mass ratio of 26:18:1:13:26:6:10 and stir for 500 seconds to mix them evenly to obtain a multi-source solid waste composite filling cementitious material.

[0078] Examples 2-3 and Comparative Examples 1-8

[0079] The difference between Example 2-3 and Comparative Example 1-8 and Example 1 is that Example 2-3 changes the raw material ratio of the multi-source solid waste composite filling cementitious material and the mechanical force activation time of the water slag, and Comparative Example 1-8 changes the raw material ratio of the multi-source solid waste composite filling cementitious material, and the rest is roughly the same as Example 1, which will not be repeated here. The mechanical force activation time of the water slag in Example 2-3 is 30min and 50min respectively, and the raw material composition of Example 1-3 and Comparative Example 1-8 is shown in Table 4.

[0080] Table 4. Raw material composition of Examples 1-3 and Comparative Examples 1-8

[0081]

[0082] Comparative Examples 9-10

[0083] The difference between Comparative Examples 9-10 and Example 1 is that the mechanical force activation time of the water slag is changed, and the other details are substantially the same as Example 1, which will not be described again. The mechanical force activation time of Examples 1-3 and Comparative Examples 9-10 and the specific surface area of ​​the water slag powder are shown in Table 5.

[0084] Table 5. Mechanical force activation time and specific surface area of ​​slag powder in Examples 1-3 and Comparative Examples 9-10

[0085] project Mechanical activation time (min) <![CDATA[Specific surface area (m 2 / kg)]]> Example 1 40 687 Example 2 3z 642 Example 3 50 673 Comparative Example 9 20 589 Comparative Example 10 60 691

[0086] As shown in Table 5, it can be seen that when the mechanical force activation time is less than 30 minutes, the specific surface area of ​​the water slag powder is too small, which is not conducive to the subsequent mixing and penetration with the gold mine tailings. When the mechanical force activation time is greater than 50 minutes, although the powder grinding can be more complete, the improvement space is small and the preparation cost will increase. Therefore, the optimal mechanical force activation time is 30-50 minutes.

[0087] Examples 4-6 and Comparative Examples 11-20

[0088] Examples 4-6 and Comparative Examples 11-20 respectively provide a filling material, which is prepared by the following method: the multi-source solid waste composite filling cementitious material prepared in Examples 1-3 and Comparative Examples 11-20 is mixed with gold mine tailings at a ash-sand ratio of 1:4, and then water is added to prepare a slurry with a mass concentration of 65%, thereby obtaining the corresponding filling material, as shown in Table 6.

[0089] Table 6. Sources of multi-source solid waste composite filling gel materials used in Examples 4-6

[0090]

[0091] Comparative Example 21

[0092] The difference between Comparative Example 21 and Examples 4-6 and Comparative Examples 11-20 is that P.O42.5 ordinary Portland cement slurry is used to prepare the filling material. Specifically, P.O42.5 ordinary Portland cement slurry is mixed with gold mine tailings in a ash-sand ratio of 1:4, and then water is added to prepare a slurry with a mass concentration of 65%, thereby obtaining the corresponding filling material.

[0093] 2. Test Method

[0094] (1) Particle size detection and analysis

[0095] The water slag powder is screened with 200 meshes by vibration screening method to prevent insufficient grinding. Then the screened water slag powder is sampled by reduction method and tested by laser particle size analyzer to check whether the surface area of ​​water slag powder exceeds 600m 2 / kg.

[0096] (2) Setting time test

[0097] The cementitious material to be tested is prepared into mortar according to a water-solid ratio of 0.5 and loaded into a round mold, and the round mold is sealed and stored in a room temperature environment of about 20°C away from light. The initial setting time is measured every 5 minutes using a Vicat instrument, and the final setting time is measured every 30 minutes after the material is initially set.

[0098] (3) Flow performance test of filling materials

[0099] Put the filling material into the round mold and turn it upside down on the vibration table, lift the round mold, turn on the vibration table switch, and let the slurry diffuse freely. When the slurry no longer diffuses, turn off the vibration table switch, measure the diffusion diameter 3 times with a ruler, and take the average value.

[0100] (4) Strength test of filling material

[0101] The filling material was placed in a 70.7×70.7×70.7mm triple test mold and cured in a concrete constant temperature and humidity standard curing box at a curing temperature of 20±1℃ and a humidity of 95%. After the curing age reached 3d, 7d and 28d, the compressive strength of the filling material was tested using an AEC-01 cement strength testing machine. 3d, 7d and 28d correspond to the early strength, mid-term strength and late strength of the filling material, respectively.

[0102] III. Analysis of test results of various embodiments and comparative examples

[0103] The setting time of the multi-source solid waste composite filling cementitious materials prepared in Examples 1-3 and Comparative Examples 1-10 was tested according to the method in Test Method (2), and the test results were compared with the setting time of P.O42.5 ordinary Portland cement paste. The test results are shown in Table 7.

[0104] Table 7. Setting time of cementitious materials prepared in Examples 1-3 and Comparative Examples 1-10 and P.O42.5 ordinary Portland cement paste

[0105]

[0106] The fluidity and strength of the filling materials prepared in Examples 4-6 and Comparative Examples 11-20 were tested according to the methods in test methods (3) and (4), and the test results were compared with the fluidity and strength of P.O42.5 ordinary Portland cement paste. The test results are shown in Table 8.

[0107] Table 8. Fluidity and strength of filling materials prepared in Examples 4-6 and Comparative Examples 11-20

[0108]

[0109]

[0110] Please refer to Table 7, it can be seen that the initial setting time of the mortar prepared by the cementitious materials prepared in Examples 1-3 is 72-87 minutes, and the final setting time is 264-301 minutes, both of which are shorter than the initial setting time and final setting time of P.O42.5 ordinary Portland cement paste.

[0111] Please refer to Table 8. First, it can be seen that since the diffusion range of the filling materials prepared in Examples 4-6 is 21.5-27.6 cm, they are all greater than the diffusion range of the filling materials prepared by P.O42.5 ordinary Portland cement slurry. This indicates that the multi-source solid waste composite filling cementitious material provided in the present application can combine more water molecules during the hydration process and has good water retention performance.

[0112] Secondly, it can be seen that since the multi-source solid waste composite filling cementitious material provided in the present application has a finer particle size and more active ingredients, the filling material prepared by mixing this cementitious material with fine-grained gold mine tailings has a better strength growth rate and performance indicators during the filling process than the filling material prepared with P.O42.5 ordinary Portland cement. Among the performance indicators, the early strength, mid-term strength and late strength of the filling material prepared with this cementitious material are all more than 20% higher than the strength of the filling material prepared with P.O42.5 ordinary Portland cement at the same age.

[0113] Again, it can be seen that the mechanical force activation time of the slag further affects the strength performance index of the filling material prepared by using the slag powder by affecting the surface area of ​​the slag powder. This is because when the mechanical force activation time of the slag is less than 30 minutes, although the setting time of the mortar is not much different from that of Example 1, when it is prepared as a filling material for filling, the cementitious material that can penetrate into the fine particles of the gold tailings becomes less, causing a certain decline in the filling effect. In this embodiment, gold tailings of fineness grade are used, and the fineness of the slag is required to be relatively high. When it is used for filling other tailings with coarser grading, the mechanical force activation time can be appropriately reduced.

[0114] Please combine Table 7 and Table 8, it can be seen that, compared with Example 1, reducing the relative content of fly ash, quicklime and cement clinker in the raw materials of Example 3 can shorten the setting time of the cementitious material, but the early strength of the filling material (Example 6) prepared by using the same is not high, because there is a lack of sufficient sulfate ions to generate calcium sulfaluminate to improve the early strength, but with the generation of a large amount of hydrated calcium aluminosilicate gel and other hydration products in the later stage, the later strength is improved; compared with Example 1, increasing the relative content of fly ash, quicklime and cement clinker in Example 2 will prolong the setting time of the cementitious material. In addition, the early strength growth rate of the filling material (Example 5) prepared by using the same is faster. As more and more calcium sulfaluminate and calcium sulfoaluminate are generated, the hydration and hardening speed of cement is faster and faster, so that the mid-term strength is also greatly increased, but because the calcium sulfaluminate structure is not stable, it does not contribute much to the growth of the later strength of the material, so the later strength is not high.

[0115] According to the above content, combined with the test results of Comparative Examples 1-4 and Comparative Examples 11-14, it can be known that the mass proportion of gypsum should be controlled below 25%, and the total amount of fly ash, quicklime, and cement clinker should decrease with the increase of gypsum dosage, or increase with the decrease of gypsum dosage, otherwise the two reaction systems will produce mutual inhibition and hinder the growth of strength. In addition, the ratio of fly ash, quicklime and cement clinker should be maintained within a certain range, especially quicklime. An appropriate amount of quicklime has excellent hydration reaction ability and can effectively improve the early and mid-term strength of the material, but too much quicklime will cause the water to boil, resulting in excessively high temperature of the reaction system, destroying the formation of the crystal structure and making the material loose.

[0116] Please continue to combine Table 7 and Table 8, and you can see that the addition and proportion of the activator have a great influence on the strength of the filling material. If the total amount of active activator added is controlled within 0.5% to 2%, it can generally play a good stimulating role to improve the strength of the filling material, but adding too much sodium hydroxide and sodium salt will lead to the occurrence of alkali efflux phenomenon, so the amount of sodium sulfate should be reduced with the increase of sodium hydroxide, or increased with the decrease of sodium hydroxide. In addition, the amount of sodium hydroxide should be as little as possible as that of water glass, so that the active stimulating process of the cementitious material is mainly water glass, and sodium hydroxide is supplementary. If necessary, less sodium hydroxide can be added or no sodium hydroxide can be added, especially when the amount of sodium sulfate added is large, so that the occurrence of alkali efflux phenomenon can be avoided.

[0117] In summary, the present application provides a multi-source solid waste composite filling cementitious material, a preparation method thereof, and a filling material containing the material. The multi-source solid waste composite filling cementitious material provided in the present application includes: 15.5-20.5 parts of gypsum powder, 10-15 parts of sodium sulfate, 22.5-27.5 parts of water slag powder, 22.5-27.5 parts of fly ash, 2.5-7.5 parts of cement clinker, 7.5-12.5 parts of quicklime, and 0.5-2 parts of active stimulant, which can be mixed with gold mine tailings or tailings of other fineness to prepare filling materials; in the preparation method of the multi-source solid waste composite filling cementitious material provided in the present application, the mechanical force activation time of water slag is 30-50min; the expansion degree of the filling material provided in the present application is 20-50cm, and the later strength is 2.3-2.5MPa, which can be used for filling mining.

[0118] The present invention uses sodium sulfate to modify the gypsum separated and extracted from the biological oxidation liquid, and dries and grinds it to obtain gypsum powder. The gypsum powder and the water slag powder activated by mechanical force constitute a sulfate reaction system. In this system, gypsum provides a part of SO for the generation of hydration products. 4 2- As well as a suitable alkaline environment, another part of the reaction requires SO 4 2-Provided by sodium sulfate, in the reaction, gypsum and sodium sulfate simultaneously stimulate the water slag to generate calcium sulfoaluminate and calcium sulfoaluminite crystals. This method effectively improves the water retention performance of the cementitious material, and promotes the early and mid-term strength improvement of the filling material and the generation of early and mid-term hydration products; in addition, the present application also introduces fly ash, quicklime, cement clinker and active stimulant to form an alkaline reaction system, which accelerates the hydration rate of the material while increasing the number of later hydration products to generate hydrated calcium silicate gel, hydrated calcium silicate and other hydration products. The calcium sulfoaluminate generated in the early coagulation process and the hydrated calcium silicate gel generated in the later stage are continuously crystallized, which promotes the continuous progress of the reaction. At the same time, through the close interweaving of the two in the material, the later coagulation strength of the material is greatly improved.

[0119] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A method for preparing a multi-source solid waste composite filling gelling material, characterized in that: The steps include: S1, mixing the water slag and water in a mass ratio of (0.8-1.2):1 to form a slag slurry, pouring it into a ball mill for mechanical activation, putting it into an oven for drying, then grinding and sieving to obtain water slag micro powder; S2, preparing a sodium sulfate solution with a concentration of 30%-80%, spraying the sodium sulfate solution uniformly on the gypsum surface without dead angles according to the expected weight portion through a spray device, drying in an oven and then grinding to obtain gypsum powder with a fineness greater than 200 mesh; S3, uniformly mixing sodium hydroxide and water glass in a mass ratio of (0-3):4 to obtain an active activator; S4, mixing and stirring the gypsum powder, the slag powder, the active activator, fly ash, cement clinker and quicklime according to the expected weight proportions to obtain the multi-source solid waste composite filling cementitious material.

2. The method for preparing multi-source solid waste composite filling gelling material according to claim 1, characterized in that: In step S1, the mechanical activation time is 30min-50min, the sieving is to sieve the water slag with 200 mesh by vibration sieving method, and the oven is set to 100-105℃ for 24-28h; the activity coefficient of the water slag powder is ≥0.25, and the specific surface area is ≥600m 2 / kg.

3. The method for preparing multi-source solid waste composite filling gelling material according to claim 2, characterized in that: In step S3, the water glass is industrial powdered sodium silicate with an effective content greater than 95% and a modulus of 1.5; the sodium hydroxide is industrial powdered sodium hydroxide with an effective content greater than 90%.

4. The multi-source solid waste composite filling cementitious material according to claim 3, characterized in that: In step S2, the oven is set to 100-105°C for 12-16 hours, and the sodium sulfate solution is prepared by using industrial powdered sodium sulfate with an effective content greater than 90%.

5. The multi-source solid waste composite filling cementitious material according to claim 4, characterized in that: In step S4, the cement clinker is silicate cement clinker, in which the total mass proportion of CaO, SiO2, Al2O3 and Fe2O3 is greater than 95%; and the quicklime is calcareous quicklime in which the mass proportion of CaO is greater than 60%.

6. A multi-source solid waste composite filling cementitious material, characterized in that: The multi-source solid waste composite filling cementitious material is prepared according to the preparation method according to claims 1-5, comprising the following raw materials in parts by weight: 15.5-20.5 parts of gypsum powder, 10-15 parts of sodium sulfate, 22.5-27.5 parts of slag powder, 22.5-27.5 parts of fly ash, 2.5-7.5 parts of cement clinker, 7.5-12.5 parts of quicklime, and 0.5-2 parts of active activator; The gypsum powder is prepared by using gypsum separated and extracted from biological oxidation liquid.

7. The multi-source solid waste composite filling cementitious material according to claim 6, characterized in that: The initial setting time of the clean slurry of the multi-source solid waste composite filling cementitious material is 40-50 minutes, and the final setting time is 380-400 minutes.

8. A filling material, characterized in that: It comprises the multi-source solid waste composite filling cementitious material and tailings as described in any one of claims 6-7.

9. The filling material according to claim 8, characterized in that: The tailings include ultra-fine gold tailings or tailings with a fineness of 100-400 meshes.

10. The filling material according to claim 8, characterized in that: The expansion of the filling material is 20-50 cm, and the later strength is 2.3-2.5 MPa.

Citation Information

Patent Citations

  • Composition for aerated concrete or lightweight aggregate concrete

    CN113698140A

  • Clinker-free fly ash composite cementing material, preparation method thereof and coal mine filling paste

    CN114213046A

  • Superfine tailing filling cementing material mainly prepared from copper slag and fly ash and filling material of superfine tailing filling cementing material

    CN116496009A

  • Cement composition and method for producing the same

    JP2019131416A

  • Cement composition

    JP2019137586A

Cited By

  • Solid waste-based cementing material with high interface bonding strength and preparation method of solid waste-based cementing material

    CN120736813A